THE INFLUENCE OF TOOTHBRUSHING BEHAVIOR BASED ON COMMUNITY CHARACTERISTICS OF TAYAN HILIR DISTRICT IN SANGGAU DISTRICT - Rusmali, Rusmali; Rita Herlina; Erma Mahmiyah (Journal of Innovation Research and Knowledge, 2024)
West Kalimantan with an individual DMF-T Index reaching 6.2, equivalent to 6-7 dental and oral health cases per person (West Kalimantan Provincial Health Office, 2017). The results of Riskesdas (2018) for Sanggau Regency regarding dental and oral health, namely 48.43% of cavities/sick teeth, 23.73% of teeth that were extracted/lost themselves, 3.0% of teeth that had fillings, while teeth with a rocking condition of 12.75%. The results of Rusmali et al.'s research in 2022 in Tayan Hilir District, Sanggau Regency regarding the influence of the incidence of dental caries (DMF-T), dental and oral hygiene status (OHI-S) on the toothbrushing behavior of young women based on areas of residence in coastal rivers and highlands of 36.8% with siq value. 0.05 ≤ 0.05. The results of research by Rusmali et al in 2023 by adding the variable type of cariogenic food that is frequently consumed was 38.9% and the age group of respondents with an average age of 13 years was 40.4%. Tooth brushing behavior influences the DMF-T figure by 15%, the area of residence influences the DMF-T figure by 8.8%, the type of cariogenic food influences the DMF-T figure by 6.3% and age influences the DMF-T figure by 7.7%. Meanwhile, tooth brushing behavior influences dental and oral hygiene status (OHI-S) 15%, area of residence influences dental and oral hygiene status (OHI-S) 10%, type of cariogenic food influences dental and oral hygiene status (OHI-S) 21, 1% and age influences dental and oral hygiene status (OHI-S) 21.3%. Siq value. 0.00 < of 0.05. This study aims to describe and analyze the influence of tooth brushing behavior based on characteristics (individual DMF-T number, category, dental and oral hygiene status (OHI-S), age, area of residence, type of food). This type of research is Experimental Quasi with one Design Research, data collection using survey sheets and direct examination using the Porpusive Sampling method, analysis used Univariate, Bivariate and Multivariate. Test using Regression.Brushing one's teeth is very important for a person to do as a habit because, by brushing one's teeth one can break the chain of growth and development of plaque. Plaque is the main cause of tooth decay. Another thing that is also very important is the time to brush your teeth which must be in accordance with the recommendations, namely twice a day, such as in the morning after breakfast and at night before bed. Instilling these habits can be done by increasing knowledge (Promotive), prevention (Preventive) and treatment (Curative).